The Coronavirus Calendar (CoronaCal): a simplified SARS-CoV-2 test system for sampling and retrospective analysis - Kazmi, Manija A.; Thaler, David S.; Åberg, Karina C.; Mattheisen, Jordan M.; Huber, Thomas; Sakmar, Thomas P. (Frontiers in Epidemiology, 2023)
Objectives: To develop a biological diary (CoronaCal) that allows people in the community to collect and store serial saliva samples and chart symptoms on ordinary printer paper. Methods: Diaries were analyzed for the presence of SARS-CoV-2 RNA using established polymerase chain reaction (PCR) procedures. CoronaCal diaries were distributed to volunteer subjects in the community during the peak of the Covid-19 outbreak in New York. Volunteers collected their own daily saliva samples and self-reported symptoms. Results: SARS-CoV-2 RNA extracted from CoronaCals was measured using qPCR and RNA levels were correlated with reported symptoms. SARS-CoV-2 RNA was detected in CoronaCals from nine of nine people with Covid-19 symptoms or exposure to someone with Covid-19, and not in one asymptomatic person. CoronaCals were stored for up to 70 days at room temperature during collection and then frozen for up to four months before analysis, suggesting that SARS-CoV-2 RNA is stable once dried onto paper. Conclusions: Sampling saliva on simple paper provides a useful method to study the natural history and epidemiology of Covid-19. The CoronaCal collection and testing method is easy to implement, inexpensive, non-invasive and scalable. The approach can inform the historical and epidemiological understanding of infections in individuals and populations.